Navigating project selection and execution for competitive advantage a guide to evaluating prospective projects at the idea stage - Triantis, John E., 1944- (New York : Productivity Press, 2021)
For many organizations, the way in which processes and projects are selected and executed is a fundamental factor in how well they can prosper in today's marketplace. By improving efficiency, driving productivity and reducing costs, organizations can increase throughput, improve service and bring new products to market faster. The aim of this book is to show how to assess chances of project success at the idea stage in order to direct resources to promising projects and conserve resources. In doing that, it presents effective project execution processes, practices, and experiences that help to select the right projects and do them right. This is a mindset changing book from project speed and cost cutting to discipline, execution excellence, and competitive advantage. It is about effective business development using a practical approach to select the right projects and do them successfully. It describes how to evaluate and predict the likelihood of project success at the idea stage before resources are expended to develop projects. Each chapter describes how to evaluate planned project development and implementation, rate its performance, and identify gaps to be filled to achieve project execution excellence. The book is designed to guide the assessment of each project stage to uncover areas in need of improvement with focus on prediction of project success. Hence, each chapter stands on its own and assesses key elements of project stages to determine how well they are executed. The journey of project execution described is based on predicting project success at the idea stage and begins with understanding differences in large project requirements and their effects on the way they should be done. The evaluation of the idea's origin and reasons for pursuing a project is done with help from an experienced facilitator/moderator. The reason for it is that this individual is engaged to assess likelihood of success from an external, independent, critical, and objective perspective before the project begins.
OCLC-licensed vendor bibliographic record.
Keywords: Research and development projects -- Evaluation; New products -- Evaluation; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Project Management